Comparative outcomes of laparoscopic and open gastrectomy for T4b gastric cancer with transverse colon or mesentery invasion: a dual-center retrospective analysis - Yi-ming Lu; Zhi-bin Ye; Hai-kuo Wang; Wen-hui Zhong; Xin-xin Shao; Hai-tao Hu; Yu-juan Jiang; Wang-yao Li; Yan-tao Tian (World Journal of Surgical Oncology)
Abstract Background The safety and feasibility of laparoscopic surgery for T4b gastric cancer with transverse colon or mesocolon invasion remain insufficiently characterized. This study aimed to compare the surgical outcomes of laparoscopic and open gastrectomy in individuals with T4b gastric cancer involving these anatomical structures. Methods A retrospective cohort study was conducted across two centers, including 53 individuals with T4b gastric cancer involving the transverse colon or mesocolon who underwent curative-intent surgery between January 2011 and December 2019. Participants were divided into two groups based on the surgical approach: laparoscopic surgery (n = 32) and open surgery (n = 21). Perioperative outcomes, postoperative complications, and survival outcomes were evaluated and compared. Results Baseline characteristics were comparable between the groups. The laparoscopic approach demonstrated significantly reduced intraoperative blood loss compared to open surgery (92.5 ± 101.9 mL vs. 147.6 ± 76.6 mL, p = 0.039). No significant differences were observed in operating time (187.8 ± 52.7 vs. 185.9 ± 52.3 min, p = 0.896), R0 resection rates (93.8% vs. 90.5%, p = 0.659), lymph node yield, or length of postoperative hospital stay. The incidence of postoperative complications was similar between the groups (10.3% vs. 10.5%, p = 0.986). Additionally, mean overall survival (31.4 vs. 27.2 months, p = 0.506) and progression-free survival (26.1 vs. 23.5 months, p = 0.573) did not differ significantly. Conclusions Laparoscopic gastrectomy with combined resection appears to be a feasible and safe alternative to open surgery for selected individuals with T4b gastric cancer involving the transverse colon or mesocolon. This approach achieves similar perioperative and long-term clinical outcomes compared to open surgery.